تصور مقترح لتطوير معايير جودة الأداء الإداري لإدارات التعليم بالمملكة العربية السعودية في ضوء معايير إدارة الجودة الشاملة من وجهة نظر المشرفين التربويين - محمدي، منصور غازي (Kulliyah of Education, International Islamic University Malaysia, 2020)
This study aims to investigate the status of educational management performance adopted by education departments in the KSA in light of the standards of total quality management and from educational supervisors' point of view. It also attempts to build and test proposed standards for the quality of administrative performance of these departments in light of the standards of total quality management and from educational supervisors' point of view. The study follows a descriptive-analytical method. The overall number of the study population is (9002) educational supervisors of (47) education departments in the KSA. These departments are divided according to the Ministry of education into five geographical areas: (North, East, West, midland, and South). Samples representing all sectors are randomly selected. To achieve the objectives of the study, a questionnaire of 119 items has been designed taking into consideration the face validity and stability test of the coefficient of Cronbach's alpha reaching general stability (0.99). The study selected sample is (369) educational supervisors and the applied analyses are: statistical (SPSS), descriptive, exploratory, EFA, CFA, AMOS, and the Smart PLS. The study concludes: the current status of the quality of educational management performance adopted by education departments in the KSA is low with an average of 1.57 and a standard deviation of 1.161 from the point of view of the educational supervisors; the importance of ten proposed criteria with an average of (4.3) and a standard deviation of (.871); alternative standards of the quality of educational management performance seem to be acceptable, significant and valid. Further, the study proposes and recommends a model that includes main and secondary standards to achieve high quality in educational management performance of education departments in the KSA equal to international quality standards.